2011
DOI: 10.1002/pmic.201100296
|View full text |Cite
|
Sign up to set email alerts
|

Peptide arrays for kinome analysis: New opportunities and remaining challenges

Abstract: Phosphorylation is the predominant mechanism of post-translational modification for regulation of protein function. With central roles in virtually every cellular process, and strong linkages with many diseases, there is a considerable interest in defining, and ultimately controlling, kinase activities. Investigations of human cellular phosphorylation events, which includes over 500 different kinases and tens of thousands of phosphorylation targets, represent a daunting challenge for proteomic researchers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
87
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 57 publications
0
87
0
Order By: Relevance
“…Ideally, to become clinically useful, technologies must provide rapid and high-fidelity analysis of small-quantity samples. Kinase substrate array technologies are high-throughput tools for global profiling of kinase activities in tissue samples without prior knowledge of which signaling pathways are activated [33][34][35][36]. Using such arrays, each tumor sample will generate an individual phosphosubstrate signature, theoretically portraying the state of composite information flow through signaling cascades.…”
Section: Kinase Profiling Technologiesmentioning
confidence: 99%
“…Ideally, to become clinically useful, technologies must provide rapid and high-fidelity analysis of small-quantity samples. Kinase substrate array technologies are high-throughput tools for global profiling of kinase activities in tissue samples without prior knowledge of which signaling pathways are activated [33][34][35][36]. Using such arrays, each tumor sample will generate an individual phosphosubstrate signature, theoretically portraying the state of composite information flow through signaling cascades.…”
Section: Kinase Profiling Technologiesmentioning
confidence: 99%
“…Monitoring global responses at the level of cellular kinase ac-tivity (the kinome) is an effective approach to understand complex biology as well as to identify therapeutic targets and biomarkers (10). Many methods have been used to assay kinase activity under different conditions, each with advantages and disadvantages (11).…”
mentioning
confidence: 99%
“…One study utilizing human primary preadipocytes, with a comparable amount of inhibitor applied, noted a complete disruption of differentiation (13). An additional study examining 3T3-L1 cells treated with rapamycin demonstrated a substantial decrease in lipid formation and moreover, a reduction in the gene expression of the adipocytic markers PPAR␼, adipsin, adducin 1/sterol regulatory element binding transcription factor 1 (ADD1/SREBP1c), and TNF receptor superfamily, member 6 (FAS) (30).…”
Section: Mst1(t183)/mst2(t180)mentioning
confidence: 99%
“…These reversible kinasedriven phosphorylation events alter protein confirmation, ultimately affecting enzymatic activity and protein-protein in-teractions leading to an array of cellular events from differentiation to gene expression, thus encompassing signal transduction. Characterization of this broad-scale signaling architecture is necessary to provide a more finite depiction of the complex signaling events directing a given cellular phenotype and aid in the understanding of the repercussions of alterations in regulation (13,14). Presently, phosphoproteomic analysis of cellular differentiation processes such as with mass spectrometry has been performed in a very limited number of independent time points that span the cellular differentiation process, and important dynamic changes in the cellular signaling architecture may have been missed (12,15,16).…”
mentioning
confidence: 99%